(untitled) (Nexo Revista Científica, 2014)
In this study, potatoes flour for instant purée was produced using national potato varieties Provento and Granola. For this, the moisture content of potatoes was determined; the results showed that the Granola variety has lower moisture range and higher dry matter. Also, the effectiveness of physicochemical treatments (temperature, reduction of atmospheric oxygen and the use of chemical reagents) was studied for inhibition of polyphenol oxidase enzyme in the potatoes. The results showed that heat treatments, without the use of chemical agents, were the best choice for enzyme inhibition. The determination of the drying curves for potato paste, with pretreatment, was conducted in a drying tunnel at 60 ° C and an air velocity of 0.2 m/s. The pre-treatments include blanching, cooking, and the use of ascorbic acid and sodium metabisulfite. The results indicated that the applying heat treatment to potatoes was sufficient to prevent enzymatic browning and also, a lower drying time is achieved. Experimental data were evaluated using Midilli model, showing a good fit with an R2 > 0.99. Also, it was found that the optimal method for the preparation of potato flour involves the following steps: cooking, cooling and dry size reduction. This ensures that the flour, according to the results of swelling power, solubility in water and water absorption, reaches instant starch characteristics favoring the formation of a puree quickly. Yields in flour production range from 12.55 to 14.09% for Granola and between 11.18 to 15.58% for Provento wet basis. DOI: http://dx.doi.org/10.5377/nexo.v27i2.1946